Assessment of the Quality and Effective Implementation of First Aid Services in Selected Secondary School in Abuja Municipal Area Council (AMAC), FCT, Abuja - Kolawole, Agnes Anike (NIU Journal of Humanities, 2020)
This study assessed the quality and effective implementation of First Aid Services in selected Secondary schools in the Abuja Municipal Area Council (AMAC) of the Federal Capital Territory, Abuja. The study aimed at finding out the quality of the First Aid services, effective implementation of First Aid services and students benefits there from. The descriptive research design was used in this study with a sample size of 322 respondents. Questionnaires were used to gather the necessary data for the study at the end of which the findings revealed that first aid services are available and effectively carried out by trained personnel in in secondary schools in Abuja Municipal Area Council. It is therefore recommended that school authorities should put more effort to provide the best first aid services in their schools. Keywords: AMAC, Assessment, effective implementation, First Aid services, Quality and Secondary Schools